1997
DOI: 10.1016/s0741-5214(97)70265-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a new prostaglandin E1 regimen in outpatients with severe intermittent claudication: Results of a multicenter placebo-controlled double-blind trial

Abstract: For the first time efficacy and safety of a new prostaglandin E1 (PGE1) regimen in the treatment of intermittent claudication were evaluated in a randomized, double-blind, placebo-controlled multicenter clinical trial. The study involved 213 outpatients with a maximum walking distance of 50 to 200 m measured on the treadmill (3 km/hr, 12% grade). After a 2-week run-in phase they received a 2-hour intravenous infusion of 60 micrograms PGE1 or placebo 5 days a week for 4 weeks. It was followed by a 4-week interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 15 publications
1
28
0
4
Order By: Relevance
“…[21][22][23] The largest published study 21 evaluated 213 patients with a maximum walking distance of 50 to 200 m at treadmill exercise. PGE 1 was infused 5 days a week for 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] The largest published study 21 evaluated 213 patients with a maximum walking distance of 50 to 200 m at treadmill exercise. PGE 1 was infused 5 days a week for 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…31 Likewise, prostaglandin E 1 , when given intravenously for 5 days per week for 4 weeks and then twice weekly for 4 additional weeks, resulted in a 37% increase in walking distance over the placebo group. 32 Finally, Brevetti and colleagues have performed a number of studies examining the clinical effect of propionyl l-carnitine in patients with intermittent claudication. In the largest of these studies, these investigators found no difference in walking distances from placebo over the course of the study until 180 days of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, quite a few patients are unsuitable for operation. Despite technical progress, the treatment of patients with inoperable chronic CLI is still challenging; most of the patients have to undergo amputation: [6][7][8][9] 33% at 6 months and 51% at 2 years. [10] SCS has been recommended to treat ischemic pain and prevent amputation in patients with inoperable CLI.…”
Section: Introductionmentioning
confidence: 99%